IMPLIKASI PROGRAM “YES I DO” OLEH PLAN INTERNATIONAL DALAM MENGURANGI PERKAWINAN ANAK DI INDONESIA (STUDI KASUS KABUPATEN SUKABUMI) - Loudy Indah Sukma; Umi O. Retnaningsih (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Indonesia is one of the countries with the highest rates of child marriage in the world. Seeing the adverse impact of child marriage, PLAN International and its partners run the "Yes I Do" program in Sukabumi Regency as one of the highest contributing districts of child marriage in Indonesia. This study will analyze how the program has implications for child marriage in Sukabumi Regency. This research uses qualitative methods and data collection techniques from documents such as official reports, books, international and national journals, news articles, and social media that answer the steps taken and their implications. Perspective of constructivism and Clive Archer's international organizational theory are used to analyze its implications both positive and negative. The results showed that the "Yes I Do" program by PLAN International had positive implications in reducing child marriage in Sukabumi Regency. The Yes I Do program makes the people of Sukabumi Regency turn into parents and young people who are more supportive of education than marrying underage. Although national statistics of child marriage have not decreased significantly, the Yes I Do program has established sustainable programs to reduce child marriage in Sukabumi Regency. Keywords: Child Marriage, PLAN International, Yes I Do Program